Continuous decline in bone mineral density and deterioration of bone microarchitecture 7 years after Roux-en-Y gastric bypass surgery. Issue 3 (March 2020) - Hansen, Stinus; Jørgensen, Niklas Rye; Hermann, Anne Pernille; Støving, Rene Klinkby
Abstract : Objective: Roux-en-Y-gastric bypass (RYGB) surgery is an effective treatment for morbid obesity. A possible overlooked side effect is negative bone metabolic consequences. Design: A seven-year prospective study following ten women and seven men after RYGB (baseline mean age 43 ± 8 years, BMI 42 ± 6 kg/m 2 ). Methods: Lumbar spine and total hip bone mineral density (BMD) using dual energy x-ray absorptiometry, distal radius and tibia bone geometry, volumetric BMD, microarchitecture and finite element estimated bone strength using high-resolution peripheral quantitative CT and biochemical markers of bone remodelling were assessed at baseline, 2 and 7 years. Results: Compared to baseline, body weight was 24 ± 10% lower after 2 years and 21 ± 11% after 7 years. During the 7 years of follow-up, radius and tibia vBMD had declined 13 ± 8% and 8 ± 7% from baseline to 2 years and further 10 ± 7% and 7 ± 8% from 2 to 7 years (all P  < 0.001). At both radius and tibia, cortical thickness declined and cortical porosity increased. From baseline to 7 years, there were clear indications of deteriorations of the trabecular network with fewer, more widely spaced and more in-homogeneously distributed trabeculae in both radius and tibia. Overall, declines in estimated bone strength of 16 ± 9% in radius and 16 ± 7% in tibia were observed (both P  < 0.001). Conclusion: Seven years after RYGB, evidence of continuous declines in BMD and ongoing deterioration of bone microarchitecture and reduced estimated bone strength compared to baseline and 2 years post-surgery results were found. These findings emphasize the need for regular assessment of bone health in patients with prior RYGB.